Myeloperoxidase Mediates Postischemic Arrhythmogenic Ventricular Remodeling - Mollenhauer, Martin; Friedrichs, Kai; Lange, Max; Gesenberg, Jan; Remane, Lisa; Kerkenpaß, Christina; Krause, Jenny; Schneider, Johanna; Ravekes, Thorben; Maass, Martina; Halbach, Marcel; Peinkofer, Gabriel; et al. (Circulation research, 2017)
RATIONALE: Ventricular arrhythmias remain the leading cause of death in patients suffering myocardial ischemia. Myeloperoxidase, a heme enzyme released by polymorphonuclear neutrophils, accumulates within ischemic myocardium and has been linked to adverse left ventricular remodeling. OBJECTIVE: To reveal the role of myeloperoxidase for the development of ventricular arrhythmias. METHODS AND RESULTS: In different murine models of myocardial ischemia, myeloperoxidase deficiency profoundly decreased vulnerability for ventricular tachycardia on programmed right ventricular and burst stimulation and spontaneously as assessed by ECG telemetry after isoproterenol injection. Experiments using CD11b/CD18 integrin-deficient (CD11b-/-) mice and intravenous myeloperoxidase infusion revealed that neutrophil infiltration is a prerequisite for myocardial myeloperoxidase accumulation. Ventricles from myeloperoxidase-deficient (Mpo-/-) mice showed less pronounced slowing and decreased heterogeneity of electric conduction in the peri-infarct zone than wild-type mice. Expression of the redox-sensitive gap junctional protein Cx43 (Connexin 43) was reduced in the peri-infarct area of wild-type compared with Mpo-/- mice. In isolated wild-type cardiomyocytes, Cx43 protein content decreased on myeloperoxidase/H2O2 incubation. Mapping of induced pluripotent stem cell-derived cardiomyocyte networks and in vivo investigations linked Cx43 breakdown to myeloperoxidase-dependent activation of matrix metalloproteinase 7. Moreover, Mpo-/- mice showed decreased ventricular postischemic fibrosis reflecting reduced accumulation of myofibroblasts. Ex vivo, myeloperoxidase was demonstrated to induce fibroblast-to-myofibroblast transdifferentiation by activation of p38 mitogen-activated protein kinases resulting in upregulated collagen generation. In support of our experimental findings, baseline myeloperoxidase plasma levels were independently associated with a history of ventricular arrhythmias, sudden cardiac death, or implantable cardioverter-defibrillator implantation in a cohort of 2622 stable patients with an ejection fraction >35% undergoing elective diagnostic cardiac evaluation. CONCLUSIONS: Myeloperoxidase emerges as a crucial mediator of postischemic myocardial remodeling and may evolve as a novel pharmacological target for secondary disease prevention after myocardial ischemia.
Keywords: Animals; Peroxidase; fibrosis; myocardial ischemia; Myocardial Ischemia; Myocytes, Cardiac; Mice, Knockout; myši knockoutované; lidé; Mice; ischemická choroba srdeční; Organ Culture Techniques; kultivované buňky; Arrhythmias, Cardiac; myši; Ventricular Remodeling; infarction; orgánové kultury - kultivační techniky; Cells, Cultured; Male; myši inbrední C57BL; Connexin 43; remodelace komor; inflammation; mužské pohlaví; zvířata; Mice, Inbred C57BL; tachycardia; peroxidasa; srdeční arytmie; kardiomyocyty; Humans